ESTIMATION OF THE MODERN MUCOLYTIC THERAPY EFFICACY IN CHILDREN, SUFFERING FROM MUCOVISCIDOSIS (TWO YEAR EXPERIENCE OF DORNASE ALFA APPLICATION) - E.B. Pavlinova; A.G. Mingairova; T.I. Safonova; T.Yu. Korneyeva ("Paediatrician" Publishers LLC, 2007)
Complications from the part of the respiratory apparatus are the main reason for the lethality among patients, suffering from mucoviscidosis. The adequate mucolytic therapy is of great importance in the complex treatment of the chronic bronchopulmonary process. In 2004, in Omsk center of mucoviscidosis, the researchers started to regularly apply a new mucolytimedication dornase alfa in treatment of children (Pulmozyme, F. Hoffmann La Roche Ltd., Switzerland). The results of the two year observation showed that dornase alfa may successfully be used in complex therapy of patients, suffering from mucoviscidosis, as well as periodical and chronic colonization of the respiratory tracts by Pseudomonas aeruginosa. Key words: mucoviscidosis, children, dornase alfa.